ANALISIS PUSH AND PULL FAKTOR YANG MEMPENGARUHI KEPUTUSAN UNTUK BERMIGRASI KE KOTA DENPASAR - Karma Putra, I Made Yusa Aditya; Marhaeni, AnakAgung (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 11 No 5 (2022): VOL 11 NO 5, MEI 2022 [1621-2044]DO - 10.24843/EEP.2022.v11.i05.p10, 2022)
The high population growth is indeed one of the priority problems that must be addressed immediately, especially in Indonesia. But on the other hand, if the population growth rate is too low it will also have a negative impact on regional development. This problem also needs attention. In essence, population mobility (migration) is a reflection of differences in growth and inequality of development facilities from one region to another. This study aims to analyze the effect of push factors (land ownership, education level) and pull factors (income, presence of relatives in the destination area) on leght of migration to Denpasar City. This research uses primary date. The date were collected by means of observation, in-depth interviews, and structured interviews. The analysis technique used in this research is moderation regression analysis. The number of samples taken in this study were 99 respondents, using accidental sampling method. Based on the results of the analysis, it was found that 1) Push factor (land ownership in the area of ??origin, education level) and pull factor (income, presence of relatives in the destination area) simultaneously affected the length of migration to Denpasar City; 2) Pull factor (income) and Push factor (education level) have a positive effect on the length of migration to Denpasar City; 3) The push factor (land ownership in the area of ??origin) has a negative effect on the length of migration to Denpasar City; 4) Migrants who have relatives in Denpasar City stay longer in Denpasar City compared to migrants who do not have relatives in Denpasar City; 5) The presence of relatives in the destination area moderates the effect of income, education level, land ownership on the length of migration to Denpasar City.